Analisis Dampak Work Life Balance terhadap Hubungan Industrial pada Perusahaan Perbankan di Indonesia - Galant Mohandirenza Ahmed; Yoga Aditiya Pratama; Mohamad Zein Saleh (CV. ITTC INDONESIA, 2025)
This study aims to analyze the impact of work-life balance on industrial relations in banking companies in Indonesia. In the context of the banking sector, which is known for its high workload and target pressure, the balance between work and personal life is an important factor in maintaining harmonious relationships between employees and management. This study uses the literature study method by reviewing various previous research results and empirical data related to work-life balance and industrial relations dynamics. The results show that work-life balance imbalances can increase job stress, reduce satisfaction, and trigger industrial conflict. Conversely, the implementation of policies that support work-life balance, such as flexibility in working hours and employee welfare programs, has been proven to improve performance, loyalty, and create more harmonious industrial relations. Thus, it is important for banking management in Indonesia to strengthen work-life balance policies as a strategy in building healthy and productive working relationships.